Herbal Therapy Education Using the Flashcard Method on Students' Knowledge Level about Acute Diarrhea at SDN 1 Pemecutan - Asti; Ni luh Kade Wiradani; Anak Agung Bagus Suryantara (LPPM STIKES Mataram, 2026)
Abstract Introduction: acute diarrhea is a global public health problem that has a major impact on child morbidity and mortality, with cases in Indonesia reaching 1,168,393 in 2023, and West Denpasar District recording the highest cases in Denpasar City, totaling 453 cases. Objective: to determine the effect of guava leaf herbal therapy education using the flashcard method on the knowledge level of SDN 1 Pemecutan students about acute diarrhea. Method: a quantitative pre-experimental design with a one-group pre-test post-test approach. Sample consisted of 52 sixth-grade students using purposive sampling. Analysis used Wilcoxon Signed Ranks Test. Results: before intervention, had poor knowledge 63.5% (mean score 12.25, SD=2.671). After intervention, all students (100%) achieved good knowledge (mean score 23.46, SD=1.627). Wilcoxon test results: Z=−6.286, p=0.000 (p<0.05), effect size r=0.872 (large effect category). Conclusion: the flashcard method significantly and substantially improved students knowledge of acute diarrhea. Educational institutions are recommended to integrate the flashcard method into the School Health Program.